Social Media Utilization in the Digital Era - Asrar Aspia Manurung; Emilia Pebriwanti Saragih; Erikawati Gurning; Irma Yani Tarigan; Mey Waty Silaban; Oktaviani Napitupulu (Indonesian Journal of Education and Mathematical Science, 2023)
This research was a descriptive qualitative literature review. This research aims to find out the use of social media in the digital age. There are several social media that are frequently used in the digital era such as Instagram, YouTube and WhatsApp. Social media also provides various benefits in various fields, especially in the fields of education and economy. In the education field, social media can be utilized as a learning media to support learning effectiveness. Meanwhile, in the business sector, social media can be used to increase sales and advertising at a more affordable cost.